Method of determining the optimal version of the piezometer of gas distribution networks of medium and high pressure - Zhila Viktor; Klochko Aleksey (E3S Web of Conferences, 2021)
The article deals with the issues of determining the optimal type of piezometric pressure graph in high-and medium-pressure gas pipelines in the design of gas distribution networks. Along with the most commonly used ways to reduce the cost of building gas distribution networks by finding the optimal configuration of gas pipelines, which give a great economic and environmental effect, it is necessary to rationally use the pressure drop provided to the network. This step in engineering practice allows you to additionally get money savings. The use of various schemes for supplying consumers with gas in cities and villages also has a great economic effect, but modern equipment allows you to make the transition to a single-stage scheme of gas distribution networks for cities. When designing gas distribution networks, the available pressure drop can be used by implementing various technical solutions, but the correct choice of pressures in the nodal points contributes to an economic effect. The designed configuration of the gas distribution network with the adopted type of piezometric graph can ensure reliable operation for a long time. The results obtained are recommended for use in the design of gas distribution networks of cities, other settlements and distribution networks of industrial enterprises